Margaret M. Pearson. China's New Business Elite: The Political Consequences of Economic Reform. Berkeley-Los Ángeles-Londres: University of California Press, 1997. 207 pp. - Anguiano Roch, Eugenio (Estudios de Asia y África, 1998)
-